Dynamic mechanical behaviour of suture interfaces as inspiration for architectured hierarchical interlocking composites. (December 2021) - Alheit, B.; Bargmann, S.; Reddy, B.D.
Abstract: Interlocking composites have become increasingly popular in recent years. A key motivation is the impressive performance of natural interlocking protective structures. A large number of these structures – from human craniums to alligator armour – contain sutures; those are soft interfaces that join adjacent stiff plates with interdigitating protrusions. These interfaces have the potential to significantly tailor the behaviour of a structure by altering the suture geometry. Hence, sutures are a strong candidate for the biomimetic design of structures with tunable mechanical behaviour. The objective of this work is to investigate the dynamic mechanical behaviour and structure–property relationship of sutures by using finite element analysis. The focus is on behaviour during three dynamic loading scenarios: predator attack, locomotion and stress wave transfer. Additionally, these loading cases are applied to several suture geometries to investigate the suture's structure–property relationship. The hyperelastic and viscoelastic behaviour of the sutures is taken into account. Among other insights, we show that sutures can be used to tailor a structure's compliance during small deformations; tailor the degree of interlocking during larger deformations; and tailor the proportion of energy that is transferred from one plate to the next during stress wave propagation. Hence, this contribution provides insight into how sutures can be used to tailor the mechanical behaviour of structures that incur dynamic loading.